Additional Evidence Against Radio-handicapping of Northern Bobwhites - D. Clay Sisson; Theron M. Terhune; H. Lee Stribling (National Quail Symposium Proceedings, 2017)
The validity of radio-telemetry to produce reliable information (e.g., survival estimates) has recently been challenged. Radio-telemetry is a widely used technique in studies of numerous species, therefore, concerns regarding potential bias in these estimates warrant further investigation. As such, and as part of a larger study, we investigated 3 aspects of potential radio-bias: 1) variation in survival distributions among treatment (newly radio-tagged) and control (previously radio-tagged) groups; 2) proportion of trapped animals censored during the traditional 7-day censor period; and 3) ramifications to cause-specific mortality through estimation of harvest rate. Kaplan-Meier survival, based on 30-day post trapping, was similar between treatment (n = 901) and control (n = 293) bobwhites for all but 1 of 8 trapping sessions during 2000-2004. In this case, treatment bobwhites (0.970, SE = 0.015) had higher survival than control birds (0.878, SE = 0.042). We determined the effect of censoring relative to sample size was inconsequential for our analysis because the proportion of bobwhites (18 out of 1,350; 0.013) meeting the criteria for censoring, i.e., dying during the first 7 days, was minimal. Censoring of these data influenced survival estimates by an average of only 0.016 (SE = 0.004; range: 0.00 - 0.04). We evaluated harvest rate by comparing first year recovery rates of banded verses radio-tagged birds during thirteen hunting seasons occurring between 1992 and 2005. Annual recovery rate was not different (P < 0.05) for banded birds and radio-tagged birds where harvest averaged 6.68% (range 3.3 - 11.7) and 6.65% (range 3.4 - 11.1), respectively. These findings are consistent with previous research demonstrating that radio-telemetry can provide reliable demographic information. However, we recommend that future researchers test for these potential effects among their data before making biological inferences.
Keywords: Colinus virginianus; northern bobwhite; radio-handicapping; southeastern USA; survival; telemetry